2019
DOI: 10.1038/s41598-019-53924-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mRNA processing at whole transcriptome level, transcriptomic profile and genome sequence refinement of Trypanosoma cruzi

Abstract: The genomic sequence of Trypanosoma cruzi, the protozoan causative of Chagas disease was published more than a decade ago. However, due to their complexity, its complete haploid predicted sequence and therefore its genetic repertoire remains unconfirmed. In this work, we have used RNAseq data to improve the previous genome assembly of Sylvio X10 strain and to define the complete transcriptome at trypomastigote stage (mammalian stage). A total of 22,977 transcripts were identified, of which more than half could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…be the most probable signal of polyadenylation start, being cytosine the most frequent nucleotide (45.3%) and thymine the less frequent (6.79%) [57]. This differs from other trypanosomatids species, as Leishmania major and T. brucei that presents a AA dinucleotide [97,98] as the most probable signal for polyadenylation.…”
Section: Transcription Of T Cruzimentioning
confidence: 87%
See 4 more Smart Citations
“…be the most probable signal of polyadenylation start, being cytosine the most frequent nucleotide (45.3%) and thymine the less frequent (6.79%) [57]. This differs from other trypanosomatids species, as Leishmania major and T. brucei that presents a AA dinucleotide [97,98] as the most probable signal for polyadenylation.…”
Section: Transcription Of T Cruzimentioning
confidence: 87%
“…Moreover, it was demonstrated that transcriptomic data may be useful to correct and re-annotate previous assembled genomes. Besides, in the case of Sylvio X10/1, RNAseq data was used to improve the previous genome annotation showing that 79.95% of the genome corresponds to the coding sequence, while the previous genomic analysis established only a 37.73% [ 57 ]. These results also suggested that the haploid genome for Sylvio X10/1 may be higher than previously reported (at least 51 Mb).…”
Section: The Genomes Of T Cruzi : a New Updatementioning
confidence: 99%
See 3 more Smart Citations